2017
DOI: 10.4317/jced.53356
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different insertion techniques on the depth of cure and vickers surface micro-hardness of two bulk-fill resin composite materials

Abstract: BackgroundThe aim of this study was to evaluate the Vickers surface micro-hardness and the depth of cure of two bulk-fill resin composites and one incremental-fill resin composite.Material and MethodsTwo Bulk-fill dental resin composites (X-tra Fil, Voco; Sonic-FillTM 2, Kerr Corporation) and an incremental-fill dental resin composite (Filtek™ Z250 XT, 3M ESPE) were used. Sixty cylindrical specimens of 4 mm thickness were prepared using split Teflon moulds. Specimens were divided into six groups (n=10) accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 25 publications
3
26
1
3
Order By: Relevance
“…11,16 When analyzing light curing conditions on both studies, composite resin samples were exposed for 20 seconds, similar to most included investigations. 14,15,31,33,34,44,45 Nevertheless, in both studies, delivered irradiance was reported between 700 and 800 mW/cm 2 which leads to a total energy dose of 16 J/cm 2 . That may be sufficient to polymerize a 2 mm increment of conventional composite resin 19,55 but it seems to be not enough for BFRCs.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…11,16 When analyzing light curing conditions on both studies, composite resin samples were exposed for 20 seconds, similar to most included investigations. 14,15,31,33,34,44,45 Nevertheless, in both studies, delivered irradiance was reported between 700 and 800 mW/cm 2 which leads to a total energy dose of 16 J/cm 2 . That may be sufficient to polymerize a 2 mm increment of conventional composite resin 19,55 but it seems to be not enough for BFRCs.…”
Section: Discussionmentioning
confidence: 87%
“…Overall, from 21 studies that assessed BFRCs microhardness, 10 reported acceptable bottom/top hardness ratios (≥0.8) for all materials whereas 9 studies showed material‐dependent outcomes . Conversely, only 2 investigations revealed non‐acceptable bottom/top hardness ratio (<0.8) for all BFRCs tested .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Another study found that bulk fill materials produce a depth of cure that is overestimated with the ISO 4049 method [13]. The research was done on bulk fill particulate resin composite, whether inserted with an incremental technique or bulk, shows that it produces a high depth of cure, using the measuring method of the Vickers hardness ratio [17]. However, little research has been conducted to measure the depth of cure of SFRCs, especially using methods other than ISO 4049.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring the hardness of the top and bottom surfaces of the resin composite can be a good indicator in determining the depth of cure. An adequate depth of cure is attained if the ratio of hardness of the bottom to the top surface is a minimum of 0.80 (80%) [17,18].…”
Section: Introductionmentioning
confidence: 99%